International Capital Movements and the Theory of Tariffs and Trade: Comment - Inada, Ken-Ichi; Kemp, Murray C. (Quarterly Journal of Economics, 1969)
Journal Article International Capital Movements and the Theory of Tariffs and Trade: Comment Get access Ken-ichi Inada, Ken-ichi Inada Tokyo Metropolitan University Search for other works by this author on: Oxford Academic Google Scholar Murray C. Kemp Murray C. Kemp University of New South Wales Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 83, Issue 3, August 1969, Pages 524–528, https://doi.org/10.2307/1880538 Published: 01 August 1969